Response hierarchy models and their application in health and medicine: understanding the hierarchy of effects - James K. Elrod; John L. Fortenberry (BMC, 2020)
Abstract Background Successful patient engagement pursuits naturally require healthcare providers to possess a detailed understanding of their target audiences, with one of the most important processes to comprehend being the manner in which they learn about particular establishments and decide to extend their patronage. While health services patronage pathways vary between and among consumers, general patronage patterns exist which can provide enlightenment regarding this important process. Achieving knowledge on this front can help healthcare providers maximize opportunities to engage audiences and acquire all-important market share. Discussion The discipline of marketing, in part, focuses on customer engagement practices and, in describing the patronage process, it often uses what are referred to as response hierarchy models. Also known as hierarchy of effects models, these representations can help healthcare providers to understand the course through which individuals become customers of given establishments, aiding them particularly in devising appeals that can accelerate the patronage process. This particular article describes response hierarchy models, presents examples, and discusses the benefits that they offer healthcare institutions in their efforts to engage patients. Conclusions As institutional viability and vitality are predicated on abilities to successfully attract and retain patients, healthcare establishments must direct keen attention toward developing associated skills. This necessitates that health and medical providers possess a detailed understanding of their target audiences, notably including the stages through which they pass on their way to becoming patrons. Response hierarchy models present the patronage process, depicting given stages, permitting insights which can assist healthcare providers in their quests to hasten desired exchange and capture market share.